(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article examines the transformation of the public administration system in Uzbekistan from 2016 to 2025. The focus is on the stages of reform, institutional mechanisms, and results achieved. Based on institutional, systemic, and comparative approaches, three key stages are identified: institutional restructuring (2016–2018), deepening administrative reforms (2019–2021), and digital transformation of public administration (2022–2025). The study’s results demonstrate a transition from a centralized bureaucratic model to a more flexible, service-oriented, and transparent governance system. Improved efficiency of public services, increased decentralization, and the active implementation of digital technologies consistent with the international concepts of New Public Management and Digital Era Governance are noted.